The Evolving Dynamics of Digital Banking: An Indian Perspective - Arora, Neelakshi; Bhatia, Shubhra; Gupta, Santosh Gupta (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Purpose: The present research aims to explore the rapidly changing perception of the customers towards digital banking services provided by Indian banks. The constructs observed under the scope of this study were the awareness and behavioural aspects, perceived risk, usefulness, accessibility, trust and cost and time saving factor. The study attempts to evaluate how the satisfaction of customers with regards to digital banking services is affected by each of these constructs.Design/ Methodology/ Approach: In order to prepare a methodical approach to the research, detailed opinion about the satisfaction of the digital banking customers was collected through a self-prepared and self-administered structured questionnaire. The relationship between the constructs was attempted to be studied through a descriptive research design. Snowball sampling was adopted while collecting data through google form. G*power suggested the sample size to be 89. Structural equation model was assessed using Smart PLS software.Findings: The result of the study clearly indicates that the perception and acceptability of the customers for E-banking services in India varies with different age groups and occupation groups. The results also reveal that the perceived risk has a direct & significant impact on the satisfaction of customers while availing E banking services as compared to the other factors like perceived accessibility, trust, usefulness, ease of use and cost & time saving which have negligible or no impact on the satisfaction level of customers. Originality Value: It was observed that there has been a lot of research work on the importance of technology adoption and the factors that influence technology adoption in the Indian setting. However, there appears to be a research deficit in terms of understanding how customers feel about technology adoption, what they want from Indian banks and what factors are actually bothering them for absolute adoption of E-banking services. This research paper tries to fill that void in the literature.